Assessment of dental caries experience of an adult population using caries assessment spectrum and treatment index - Abhishek Mehta (Wolters Kluwer Medknow Publications, 2017)
Background: Dental caries is a pandemic disease affecting whole of the mankind. Methods of recording caries in a population are plenty, but researchers are still searching for an ideal caries recording system. Caries assessment spectrum and treatment (CAST) index is one such attempt where investigators' records spectrum of caries effects in an individual based on different codes and criteria. Materials and Methods: A cross-sectional survey was conducted on 224 adults of different socioeconomic (SE) background and their caries experience was recorded using CAST index. Kuppuswamy's scale was used to record SE status of individuals. SPSS version 17 was used for data analysis. Results: Of the 224 adults, 34.8% were suffering from chronic pulpitis and 10% had at least one tooth with periapical abscess/fistula in their mouth. Overall prevalence of caries was 45.9% and caries experience (decayed, missing, filled [DMF]) was 2.09 in the study population. Majority of subjects belonged to middle SE class. Conclusion: From the results of the present study, it is clear that CAST index is a simple, useful, and much more comprehensive tool in recording caries experience in a population than conventional DMF index.